(untitled) - Helliwell, Margaret (Cambridge, 2014)
Each level of the Student's Book has 10 units. Designed to be easy and enjoyable to teach, each unit features integrated skills and language practice. Units also include cultural awareness sections that connect learners to their region and beyond. In addition, TOEIC-style practice sections allow students' progress to be measured.
Keywords: English language,Tiếng Anh; Study and teaching,Dạy và học